Ergonomic problems in Universiti Utara Malaysia lecturers’ room - Norani, Nordin (Universiti Malaysia Perlis (UniMAP), 2014)
National Symposium on Advancements in Ergonomics and Safety (ERGOSYM2009), 1st – 2nd December 2009, Perlis, Malaysia